Addressing the autism mental health crisis: the potential of phenomenology in neurodiversity-affirming clinical practices - Pantazakos, Themistoklis; Vanaken, Gert-Jan (Frontiers in Psychology, 2023)
The neurodiversity movement has introduced a new era for autism research. Yet, the neurodiversity paradigm and the autism clinic remain largely unconnected. With the present work, we aim to contribute to filling this lacuna by putting forward phenomenology as a foundation for developing neurodiversity-affirming clinical interventions for autism. In the first part of this paper, we highlight that autistic people face a severe mental health crisis. We argue that approaches focused on reducing autistic ‘symptoms’ are unlikely to solve the problem, as autistic mental health is positively correlated with autism acceptance and perceived quality of support provided, not necessarily with lack of ‘symptomatologic severity’. Therefore, the development and dissemination of neurodiversity-affirming clinical interventions is key for addressing the autism mental health crisis. However, therapists and researchers exploring such neurodiversity-affirming practices are faced with two significant challenges. First, they lack concrete methodological principles regarding the incorporation of neurodiversity into clinical work. Second, they need to find ways to acknowledge rightful calls to respect the ‘autistic self’ within the clinic, while also challenging certain beliefs and behaviors of autistic clients in a manner that is sine qua non for therapy, irrespective of neurotype. In the second part of the paper, we introduce phenomenological psychology as a potential resource for engaging with these challenges in neurodiversity-affirming approaches to psychotherapy. In this vein, we put forward specific directions for adapting cognitive behavioral and interpersonal psychotherapy for autism.